تطوير كتاب تعليم اللغة العربية في ضوء المدخل السياقي في المدرسة الثانوية الإسلامية الحكومية الثانية بفري فاري سولا ويسي الجنوبية - Andi Arif Pamessangi (Al-Ishlah: Jurnal Pendidikan Islam, 2018)
The purpose of this research is 1) to developing the Arabic learning book based onContext Approach in Islamic Senior High School (MAN) II Parepare South Celebes.2) And to know the effectiveness of this book in Arabic learning in Islamic SeniorHigh School (MAN) II Parepare South Celebes. Researcher write this researchbecause the needed of student in Islamic Senior High School (MAN) II ParepareSouth Celebes to learning book and learning materials that’s relate with them socialand culture context. And the reason of this problem because in there is not anotherlearning book and learning materials, but the materials of Arabic learning just froma learning book that develop based on 2013 curriculum that using in thisschool.Beside that theory of process developing a learning book have to relate withstudents ability and them social culture context, because the social culture context isa basic of developing the learning book.This research uses Research andDevelopment method (R&D). In this research, researchers found 1) the Arabiclearning book based on Context Approach in Islamic Senior High School (MAN) IIParepare South Celebes, that have characteristic; a) developing based on studentcontext that is them social and culture, b) the materials learning consider oflanguage elements, that is vocabulary and syntax, and then language ability, that islistening, speaking, reading, and writing. c) examples of this book is the studentdaily context. d) exercise of this book developing based on student daily context. 2)using of Arabic learning book that be developed based on Context Approach iseffective in Arabic learning in Islamic Senior High School (MAN) II Parepare SouthCelebes. That is seeing in the result of trying in experiment class and control classwith the t result 3,234 > t table in 5% (2,719) and 1% (2,074).